1996
DOI: 10.1103/physrevb.53.r11934
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circular x-ray-dichroism study of Co/Pt(111)

Abstract: Magnetic circular x-ray-dichroism measurements at the Co L 2,3 edges of the Co/Pt͑111͒ interface are presented. Ultrathin Co films, deposited and measured at room temperature, order magnetically above a thickness of 1.8 monolayers and show magnetic anisotropy perpendicular to the surface up to coverage of at least 5 monolayers. An enhancement of the orbital magnetic momentum relative to the bulk value of Co metal is observed. A further increase after addition of a thick Pt overlayer reveals the influence of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 29 publications
4
15
1
Order By: Relevance
“…5(d) it is obvious that attributing the anisotropy of the nanostructures entirely to the surface or interface fails because the green curve is far too broad. In addition, the inferred value of E a = 0.047 ± 0.005 meV/atom is comparable to Co bulk, making difficult any reconciliation with typical thin film values of 0.1-0.2 meV/atom [14,44,45]. The blue curve fits our data much better and associates E a = 0.57 ± 0.05 meV to the perimeter atoms and zero contribution to the surface atoms in the interior of the islands.…”
Section: Quantifying the Contribution Of Perimeter Vs Surface Atoms supporting
confidence: 67%
See 1 more Smart Citation
“…5(d) it is obvious that attributing the anisotropy of the nanostructures entirely to the surface or interface fails because the green curve is far too broad. In addition, the inferred value of E a = 0.047 ± 0.005 meV/atom is comparable to Co bulk, making difficult any reconciliation with typical thin film values of 0.1-0.2 meV/atom [14,44,45]. The blue curve fits our data much better and associates E a = 0.57 ± 0.05 meV to the perimeter atoms and zero contribution to the surface atoms in the interior of the islands.…”
Section: Quantifying the Contribution Of Perimeter Vs Surface Atoms supporting
confidence: 67%
“…The second point can be at first sight surprising because it contradicts several results on Co/Pt(111) [43,44,[59][60][61][62] and on multilayered Co/Pt [14,45,63] and Co/Pd [64][65][66] films all showing out-of-plane anisotropy. However, three theoretical works show the ideal Co monolayer on Pt(111) [42,67] and Pd(111) [68] to have in-plane anisotropy, the later result having been experimentally proofed [69].…”
Section: Quantifying the Contribution Of Perimeter Vs Surface Atoms contrasting
confidence: 40%
“…[41][42][43][44] or Co/Pt systems. 43,[45][46][47] With spin LEDs integrating out-of-plane magnetic media, Sinsarp et al 48 obtained 1.5% as a lower estimate of the helicity of the light emitted at remanence at room temperature with an FePt/MgO spin injector. Hovel et al 15 have more recently demonstrated a spin injection efficiency of about 3% at remanence using mixed 3d/4f transition metal/rare earth (Fe/Tb) media.…”
Section: Introductionmentioning
confidence: 99%
“…The change of crystal fields and hybridization also affect the DOS. There are many reports supporting enhanced orbital moments for several film systems theoretically [3] and experimentally [4][5][6][7][8], although in some cases reduced orbital moments are also measured [5]. The hybridization effect was emphasized in Co/Cu(100) [5] and Co/Pt [7,8] systems, and the lowering of symmetry was considered important in Co/Cu(100) [4].…”
mentioning
confidence: 99%